Routledge handbook of EU-Middle East relations - Bouris, Dimitris; Huber, Daniela; Pace, Michelle, 1970- (New York, NY : Routledge, 2022)
"EU-Middle East relations are multifaceted, varied and complex, shaped by historical, political, economic, migratory, social and cultural dynamics. Covering these relations from a broad perspective that captures continuities, ruptures and entanglements, this handbook provides a clearer understanding of trends, thus contributing to a range of different turns in International Relations. The interdisciplinary and diverse assessments through which readers may grasp a more nuanced comprehension of the intricate entanglements in EU-Middle East relations are carefully provided in these pages by leading experts in the various (sub)fields, including academics, think-tankers, as well as policymakers. The volume offers original reflections on historical constructions, theoretical approaches, multilateralism and geopolitical perspectives, contemporary issues, peace, security and conflict and development, economics, trade and society. The chapters adopt various research methodologies organised into six main sections: History; Theoretical perspectives; Multilateralism and Geopolitical perspectives; MENA-EU relations in the contemporary world; Peace, security, and conflict in the Middle East; and Development, economics, trade and societal issues. This Handbook provides an entry point for an informed exploration of the multiple themes, actors, structures, policies and processes that mould EU-Middle East relations. It is designed for policymakers, academics and students of all levels interested in politics, international and global studies, contemporary history, regionalism and area studies"--
Keywords: Arab-Israeli conflict -- Peace; European Union countries -- Foreign relations -- Middle East; Middle East -- Foreign relations -- European Union countries; European Union countries -- Economic policy -- 21st century; Middle East -- Economic policy -- 21st century; POLITICAL SCIENCE / International Relations / General